Effect of Mutations in Hemagglutinin and Neurominidase on the Properties of Seasonal Influenza Viruses - Zadorozhna, V.I.; Liulchuk, M.G.; Shahinian, V.R.; Serheieva, T.A.; Vynnyk, N.P.; Vynograd, N.O.; Marychev, I.L.; Задорожна, В.І.; Люльчук, М.Г.; Шагінян, В.Р.; Сергеєва, Т.А.; Винник, Н.П.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2026)
Seasonal influenza viruses are pathogens that pose a constant threat to human health. They circulate everywhere and cause seasonal rises in the incidence of varying degrees of intensity in the Northern and Southern Hemispheres. These viruses are characterized by variability both due to antigenic drift and connection with the ability to reassort genes. It is known that certain amino acid substitutions in the hemagglutinin (HA) of the virus contributed to its transition to the use of human cellular receptors, which caused pandemics. The aim of the work was to analyze the literature data on the possible impact of mutations in HA and neuraminidase (NA) of seasonal influenza viruses (A(H1N1)pdm09, A(H3N2), B/Victoria)) on their properties, epidemic potential, and degree of clinical manifestation of the disease. The B/Yamagata influenza virus has not been analyzed because its circulation has effectively stopped amid the COVID-19 pandemic. It has been shown that influenza viruses A(H1N1)pdm09, A(H3N2), and B/Victoria differ significantly in terms of evolution. In dynamics, it was demonstrated the amino acid substitutions that occurred in the HA and NA of influenza viruses, including those that affected antigenic properties, resistance of viruses to specific drugs, and clinical symptoms of influenza. Those mutations that contribute to the increase in the reproduction of viruses in cell cultures and chicken embryos and affect certain biological properties of the virus are also considered. Data on the comparison of mutations in influenza viruses of different clades and viruses circulating in different geographical areas are presented. It is shown that under virtually the same initial conditions, the A(H3N2) virus among other influenza viruses showed significantly higher epidemic activity against the background of the pandemic. In the future, as was observed before, the intensity of its circulation will decrease, and the prevalence of other influenza viruses will increase, to which a layer of susceptible population will accumulate over the time. During the pandemic, the circulation of B/Victoria viruses was significantly lower than that of A viruses, especially during the first pandemic seasons. B/Victoria viruses are characterized by less pronounced HA variability than influenza A viruses. The higher antigenic stability of the virus contributes to the longer circulation of certain genetic variants of the virus with a relatively stable level of intensity and the longer use of the same vaccine variants of the viruses. Despite the large amount of data on monitoring the evolution of seasonal influenza viruses and studying the impact of amino acid mutations in HA and NA on the biological properties of the virus, their epidemic potential, and virulence potential, there are still many issues that need to be studied.